2021
DOI: 10.3390/molecules26010247
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria as Natural Therapeutics and Pharmaceutical Potential: Role in Antitumor Activity and as Nanovectors

Abstract: Cyanobacteria (blue-green microalgae) are ubiquitous, Gram-negative photoautotrophic prokaryotes. They are considered as one of the most efficient sources of bioactive secondary metabolites. More than 50% of cyanobacteria are cultivated on commercial platforms to extract bioactive compounds, which have bene shown to possess anticancer activity. The chemically diverse natural compounds or their analogues induce cytotoxicity and potentially kill a variety of cancer cells via the induction of apoptosis, or alteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 135 publications
0
37
0
Order By: Relevance
“…Among phytoplankton groups known to produce secondary bioactive metabolites, cyanobacteria are one of the most studied. Although these organisms are mainly known to produce toxins which may cause a variety of problems to human and environmental health (Chorus & Welker, 2021), some studies have shown that these secondary metabolites can be helpful to human health because of their immuno-enhancer and anticancer property (Jensen et al, 2001;Qamar et al, 2021). Moreover, the potential allochemical role of these substances has been proposed as a source of natural alternatives to synthetic pesticides (Berry et al, 2008).…”
Section: Provisioning Servicesmentioning
confidence: 99%
“…Among phytoplankton groups known to produce secondary bioactive metabolites, cyanobacteria are one of the most studied. Although these organisms are mainly known to produce toxins which may cause a variety of problems to human and environmental health (Chorus & Welker, 2021), some studies have shown that these secondary metabolites can be helpful to human health because of their immuno-enhancer and anticancer property (Jensen et al, 2001;Qamar et al, 2021). Moreover, the potential allochemical role of these substances has been proposed as a source of natural alternatives to synthetic pesticides (Berry et al, 2008).…”
Section: Provisioning Servicesmentioning
confidence: 99%
“…Numerous studies demonstrated antibacterial, antifungal, anti-tuberculosis, immune-depressing and anti-inflammatory properties of these bioactive compounds (Vijayakumar & Menakha, 2015;Rojas et al, 2020;Demay et al, 2021). Several species of cyanobacteria, cultivated on commercial platforms to obtain bioactive substances, are used in contemporary nanotechnological systems of selective transport of drugs to the tumours (Qamar et al, 2021).…”
Section: Marine Organisms Producing Cytotoxic Compoundsmentioning
confidence: 99%
“…These natural products are often the result of an evolutionary process providing competitive advantages to their producers in their natural environments. Therefore, many of these natural products have notable biological activities, making them good candidates for drug development [ 3 , 4 , 5 ], including against infectious diseases such as malaria and tuberculosis.…”
Section: Introductionmentioning
confidence: 99%